Essay and literature of thought in Spain. 2007 (XXI Century. Spanish Literature and Culture, 2017)
This work analyzes the Spanish essay’s most important contributions of 2007. The thematic variety of the essay is evident, encompassing from profound philosophical reflections to books generally classified as “self-help.” The essays achieved provide a balance between high-minded thought and lighthearted entertainment. The article pays special attention to the most important philological essays.
Keywords: Essay; philosophy